2016
DOI: 10.1038/pcan.2015.58
|View full text |Cite|
|
Sign up to set email alerts
|

Association between statins and clinical outcomes among men with prostate cancer: a systematic review and meta-analysis

Abstract: Our systematic review found that statin significantly reduced the all-cause and prostate cancer-specific mortality and improved the BCR in certain subgroup of men with prostate cancer. In future, randomized controlled trials should be conducted to establish efficacy of statins among men with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 53 publications
6
44
2
2
Order By: Relevance
“…13 Furthermore, hyperinsulinemia arising from ceramideinduced insulin-resistance may activate insulin/insulin-likegrowth-factor-1-regulated mitogenic and anti-apoptotic pathways in cancer cells. 23 However, data are limited and conflicting for statin usage in CRPC, with one study reporting the lack of survival benefits of statin on CRPC patients treated with abiraterone. [16][17][18][19] Statin therapy reduces the plasma levels of ceramides, sphingomyelin and cholesterol in individuals with cardiovascular disease or metabolic syndrome, [20][21][22] suggesting that such therapy could convert the high risk lipid profile of CRPC patients to a low risk lipid profile and thereby improve their prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Furthermore, hyperinsulinemia arising from ceramideinduced insulin-resistance may activate insulin/insulin-likegrowth-factor-1-regulated mitogenic and anti-apoptotic pathways in cancer cells. 23 However, data are limited and conflicting for statin usage in CRPC, with one study reporting the lack of survival benefits of statin on CRPC patients treated with abiraterone. [16][17][18][19] Statin therapy reduces the plasma levels of ceramides, sphingomyelin and cholesterol in individuals with cardiovascular disease or metabolic syndrome, [20][21][22] suggesting that such therapy could convert the high risk lipid profile of CRPC patients to a low risk lipid profile and thereby improve their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of observational studies on statin usage in primary prostate cancer showed that statin usage was associated with a reduced rate of relapse and prostate cancer-specific mortality. 23 However, data are limited and conflicting for statin usage in CRPC, with one study reporting the lack of survival benefits of statin on CRPC patients treated with abiraterone. 24 The beneficial effects of statin on CRPC survival may be dependent on the lipid profile of the patients, and thus our lipid signature would be useful in identifying such patients.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the effects found by these studies, along with study size, show why they attracted attention: a 22% reduction in cancer deaths among 146,326 women, 13 no effect on breast cancer incidence among 79,518 women, 14 40% reduction in prostate deaths among 22,110 high-risk patients with prostate cancer, 15 14% reduction in all-cause mortality in 2,142 patients with pancreatic cancer, 16 18% reduction in recurrence and/or deaths in 8,010 patients with breast cancer, 17 and 29% reduction in breast cancer mortality from a meta-analysis of 12 studies covering 87,951 patients with breast cancer. 18 There have also been other large studies that have reported that statins, usually when still taken after diagnosis, can reduce recurrence or mortality in patients with esophageal, 19 colorectal, 20 and lung cancer, 21 and all tumors combined, 22 with further evidence from meta-analyses of all cancers, 23 and prostate (postradiotherapy) 24,25 and colorectal cancer. 26 However, all studies were observational and none established a dose-response for statin efficacy.…”
Section: Introductionmentioning
confidence: 98%
“…Аналогичные ре-зультаты получены и в мета-анализе 26 РКИ (170000 участников) для пациентов разных возрастных групп [39]. Более того, в последние годы опубликовано значительное число исследований и систематических обзоров, в которых применение статинов ассоцииро-валось со снижением риска развития раков различной локализации и смертности от них [40][41][42][43][44], хотя от-дельного анализа данных пожилых пациентов в этих ис-следованиях не проводилось.…”
Section: Lipid-lowering Drugs In the Elderlyunclassified